User Interface Redesign an Existing Digital Invitation Platform Using User Centered Design Method - Fata Nidaul Khasanah; Muhammad Rizki Aziz; Dwi Budi Srisulistiowati (Telkom University, 2025)
The rise of digital invitations has transformed how people create and share event information, with many platforms now offering online invitation services. One such platform, which serves as the object of this study, provides invitation catalogs through its website but faces issues related to user interface (UI) design and inefficient template selection that negatively impact user experience (UX). This research aims to redesign the interface of the digital invitation platform to enhance usability and user satisfaction by applying the User-Centered Design (UCD) method. The study followed the four stages of UCD: (1) understanding the user context, (2) specifying user requirements, (3) designing solutions, and (4) evaluating the design. The context analysis identified two primary user groups—engaged couples and general users. In the requirement specification stage, low-fidelity wireframes were developed to visualize preliminary design ideas. The solution design stage produced high-fidelity prototypes with more refined visual elements, including colors, typography, icons, images, and interactive components such as buttons and navigation using Figma. Finally, the evaluation stage was conducted using the System Usability Scale (SUS). The results indicated that engaged couples achieved a SUS score of 84, while general users scored 83.5. Both results fall into Category A (Excellent), suggesting that the redesigned interface is highly usable, easy to learn, and provides a satisfying user experience. These findings highlight the effectiveness of the UCD approach in optimizing digital platforms, particularly those aimed at event and invitation services.